1972
DOI: 10.1139/v72-131
|View full text |Cite
|
Sign up to set email alerts
|

Phase Relationships in the Calcium Chloride – Calcium Carbide System

Abstract: The system calcium chloride – calcium carbide has been examined by thermal analysis. The depression of the freezing point of CaCl2 by CaC2 is ideal. The system is a eutectic one, with a eutectic point at 90 mol% CaCl2 at 740 °C. Carbon is believed to be present in the electrolyte as the so called acetylide ion [Formula: see text] The melting point of pure CaCl2 was found to be 775.2 ± 0.6 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

1976
1976
1990
1990

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 1 publication
0
4
1
Order By: Relevance
“…Dewing's solubility model (AI~CF2) Eq. [2], does not fit the data of the present work at low NaF/A1F3 molar ratios. As mentioned, a large number of other models have also been tested, but none has been found that give nearly as good prediction of the concentration of dissolved aluminum carbide in NaF-A1F3 melts as the model represented by Eq.…”
Section: A14c3(diss) + 12naf(1) = 3c(s) + 12na(diss) + 4a1f3(diss)contrasting
confidence: 85%
See 2 more Smart Citations
“…Dewing's solubility model (AI~CF2) Eq. [2], does not fit the data of the present work at low NaF/A1F3 molar ratios. As mentioned, a large number of other models have also been tested, but none has been found that give nearly as good prediction of the concentration of dissolved aluminum carbide in NaF-A1F3 melts as the model represented by Eq.…”
Section: A14c3(diss) + 12naf(1) = 3c(s) + 12na(diss) + 4a1f3(diss)contrasting
confidence: 85%
“…For 2 < CR < 4.5, Dewing obtained a good fit between the measured solubilities and the following dissolution reaction AI4C3 + 2AIF3 = 3AI2CF~ [2] Electrodeposition of amorphous carbon has been reported both for cathodic polarization of the working electrode in molten carbonates (4)(5)(6) and for anodic polarization in melts containing dissolved CaC2 (7,8). In the latter case, the overall anodic reaction was proposed to be (7) C2 ~ = 2C(s) + 2e [31…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…These reactions are confirmed by the presence of CaC2 in the electrolyte as indicated by the x-ray analysis. Calcium carbide has been reported to be soluble in this type of electrolyte (17). The formation of CaC2 also contributed to an increase in the weight of the crucible content, shown in Table I.…”
Section: Consumable Carbon Anodes--figurementioning
confidence: 96%
“…Arakawa et al (15) and Tobishima et al (16) report a high cycling stability of Li in the mixed solvent electrolyte LiAsF6-EC/2MeTHF within the voltage limits of 2.0-3.5V. Recently, Shen et al (17) confirmed the favorable effect of EC as a cosolvent of 2MeTHF/THF on the cycling efficiency (E) of Li.…”
Section: Introductionmentioning
confidence: 96%